Effectiveness of Focus Group Discussion Education on Health Cadres Knowledge of Managing Butterfly Pea Flowers and Red Guava Leaves - Norhaini Majid; Natasya Gabryella Trisagita; Muflih Muflih; Fransiska Lanni; Rahayu Widaryanti; Fika Lilik Indrawati; Reynold Padagas (Jurnal Keperawatan Respati Yogyakarta, 2023)
Public knowledge concerning health, particularly the management of medicinal plants in both community and household settings, remains limited. Enhancing knowledge can be achieved through various interventions, such as focus group discussions (FGDs). This study aims to examine the impact of FGD education on improving the understanding of Butterfly Pea Flowers (Clitoria ternatea) and Red Guava Leaves (Psidium guajava L.) management on health cadres’ knowledge in Srimartani Village, Piyungan, Bantul, Yogyakarta. The research is categorized as a quasi-experimental group pre- and post-test, with a sample size of 14 participants from the female farmer group (known as Kelompok Wanita Tani/KWT in Indonesia) chosen via purposive sampling. The FGD education consisted of the opening, implementation, and closing phases, while data analysis employed a questionnaire and quantitative research techniques utilizing the Wilcoxon test (alpha = 0.05). The findings revealed that the average knowledge scores of the respondents increased from 7.43 to 20.64 after the FGD educational intervention. The Wilcoxon test yielded a p-value of 0.001, indicating a significant effect of FGD education on the management of butterfly pea flowers and red guava leaves. Therefore, FGD education demonstrated a noteworthy influence on knowledge of Clitoria ternatea and Psidium guajava management in Srimartani Village, Piyungan, Bantul, and Yogyakarta.